COVID-19 and territorial inequalities within the Metropolitan Areas of Valparaíso, Santiago and Concepción, Chile - Fuenzalida, Manuel (2020)
This research analyzes the territorial inequalities in morbidity and mortality due to COVID-19 within the Metropolitan Areas of Valparaíso, Santiago and Concepción. The data is extracted from the 40th epidemiological report of COVID-19 and for the proxy of the Social Determinants of Health (DSS) 8 variables or social indicators are used from current information sources of the Ministry of Social Development and the National Institute of Statistics. The methodology used contemplates Exploratory Analysis of Spatial Data uni and bi varied, the construction of a DSS Index (IDSS) and the assessment of the morbidity-mortality relationships due to COVID-19 with the IDSS. The analysis of spatial distribution will be assessed from the position of each territory in the respective quadrant. The results obtained allow us to elucidate observable and comparable gaps within the communes that make up the Metropolitan Areas investigated. COVID-19 tends to generate a greater impact on morbidity when conditions of multidimensional poverty and overcrowding worsen. In terms of mortality, the territorial distribution of risk groups determines the impact and the possible definition of differentiated strategies to limit health damage.